2003
DOI: 10.1046/j.1460-9592.2003.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Target concentration of propofol required to insert the laryngeal mask airway in children

Abstract: The target-controlled infusion technique for anaesthesia induction and insertion of the LMA was a safe and effective technique in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(35 reference statements)
0
8
0
1
Order By: Relevance
“…Anesthesiologists commonly encounter airway complications during LMA insertion such as coughing, gagging, hiccups, or aspiration [15]. However, the LMA can be inserted smoothly after suppression of airway reflexes with adequate anesthesia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesiologists commonly encounter airway complications during LMA insertion such as coughing, gagging, hiccups, or aspiration [15]. However, the LMA can be inserted smoothly after suppression of airway reflexes with adequate anesthesia [16].…”
Section: Discussionmentioning
confidence: 99%
“…2527 Propofol is a highly lipophilic agent and therefore the concentration of propofol is relatively high (22–112 μM/4–20 μg/ml) in lipid-rich tissues such as the brain. 2832 Different doses of propofol have been reported to induce neurotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…3134 The dose of propofol used clinically in children varies widely but typically ranges from about 1–10 μg/mL (blood concentration) with higher doses used for induction of anesthesia and lower doses used for maintenance. 3537 In addition, cell culture and whole animal studies have shown that propofol can induce toxicity at high doses or prolonged exposure times after a single exposure. 5,31,38,39 Thus, 2-week-old hESC-derived neurons were treated with 0, 5, 10 and 20 μg/mL of research grade propofol (0–112 μM, Sigma-Aldrich) or equal volume of dimethyl sulfoxide (DMSO, Sigma-Aldrich) as the vehicle control in 60 mm culture dishes (500,000 cells/dish) or 12 mm glass coverslips (100,000 cells/coverslip).…”
Section: Methodsmentioning
confidence: 99%